식품폐수 처리시스템의 최적화 방안 연구 - 이진영 (The Graduate School, Ajou University, 2005)
Improvement of living standards caused by successful industrialization in Korea led large-scaled food processing to satisfy demand for various favorite food as well as demand for increasing population. And the amount of water demand has been increased every year. Since the pollution of rivers which has been a key role for water supply, unit processes which can remove nitrogen and phosphate as well as organic materials in wastewater from various industry is required Ministry of environment highly recommend renovation method by changing operation methods. And retrofitting is recommended when renovation is difficult to meet effluent criteria. In this study, process optimization was carried out by renovation of operating methods without installation of additional structural construction for wastewater treatment system of S food industry. S food company produces mostly soy sauce and bean paste, and discharge 450㎥/day of wastewater. Since soy bean and wheat is used as raw material, wastewater with little heavy metal and toxicant shows high concentration and excellent biodegradability. Therefore, wastewater can be efficiently treated by biological treatment. However, since the flowrate and characteristics of wastewater are fluctuated with production schedule, it is necessary to operate the equalization basin efficiently in order to minimize the fluctuation of loading rate. For the successful operation of biological system, equalization basin should be aerated and stirred to prevent anoxic condition and be installed with different level switches and measuring devices for flowrate into following process to minimize the variation in biological process and post treatment process. Existing biological treatment system was modified from conventional activated sludge process into a kind of MLE process by using primary clarifier as anoxic basin in order to meet effluent criteria for nitrogen. However, there are some operational problems such as unstable operation and high operation cost. In order to solve the above problems, lab- scaled reactors were operated with different organic loading rate, nitrogen loading rate, internal recycle ratio, and different volume ratio of anoxic and oxic tank. Existing coagulation and flocculation tank as a post treatment process followed by biological process is too big for existing flowrate of wastewater, 450㎥/day. Therefore, operation specification such as detention time and mixing intensity must be modified.
학위논문(석사)--아주대학교 대학원 :환경공학과,2005